The efficacy of Dianthus caryophyllus leave extracts against some Bacterial species - Reem Amhemmed Masoud (African Journal of Advanced Pure and Applied Sciences, 2025)
the average diameters and areas of inhibition zones indicative of growth suppression by Dianthus caryophyllus extracts were systematically analyzed against staphylococcus aureus. Streptomycin exhibited the most significant antibacterial effect, surpassing plant extracts in efficacy. Notably, the first extract of D. caryophyllus leaves demonstrated the highest antibacterial activity with a diameter area of 17.88 ± 3.72, while extract 3 showed a diameter area of 7.88 ± 2.57, with a statistically significant variation at (P<0.05). The average diameters and areas of growth inhibition zones produced by D. caryophyllus extracts against pseudomonas sp bacteria were accurately recorded for analysis. Among the tested agents, Gentamycin exhibited the most pronounced effect, achieving a diameter measure of 20.88 ± 6.03. The first extract of D. caryophyllus leaves yielded a diameter area of 13.44 ± 1.23, while the third extract showed a lower diameter area of 6.88 ± 1.36, with a notable variation at (P<0.05). This evaluation involved systematic determination of average diameters and areas of growth inhibition zones elicited by the extracts against Klebsella sp bacteria. Streptomycin displayed the most significant antibacterial effect, with an impressive diameter of 21.77 ± 2.77. The first extract of D. caryophyllus leaves generated a significant diameter area of 12.55 ± 1.94, while extract 3 exhibited a lower diameter area of 6.44 ± 2.24, both showing a statistically significant variation at (P<0.05).